Characterization of rubber degradation in a brake wheel cylinder under cyclic loading / Abdul Hakim Abdullah ... [et al.] - Abdullah, Abdul Hakim; Abd Wahid, Muhammad Fakhruddin; Mohd Samsuddin, Noorazizi; Solihin, Zainoor Hailmee; Adull Manan, Nor Fazli (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
Rubber has been widely employed in the automotive industries in various components. One component that benefits rubber is the braking system which is essentially for stopping the vehicles safely. This investigation intends to characterize the rubber degradation by applying pre-determined cyclic loadings; 10,000, 100,000, and 500,000 cycles which implicated the deformation of this rubber in the brake wheel cylinder while in service. The residual compression properties of rubbers were determined by using a uniaxial compression test. The damage development in rubbers was characterized using X-ray crystallography (XRD), pyrolysis gas chromatography-mass Spectrometry (GC-MS), and scanning electron microscope (SEM). The result indicates the rubber degradation is clearly visualized in the compression test for which lower stiffness is associated with higher cycle specimens. There is evidence of microcracks formation in SEM images which indicates the softening effect of the 100,000 cycles sample. There is a positive correlation between the number of cycles and the peak height intensity in the programs of GC-MS. In addition, the XRD results indicate evidence of crystallization reduction on the damaged samples as samples degrade under cyclic loading.